2014
DOI: 10.1371/journal.pone.0099127
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Negatively Regulates T Cell Activation to Prevent Follicular Helper T Cells and Germinal Center Formation

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a transcription factor that regulates lipid and glucose metabolism. Although studies of PPARγ ligands have demonstrated its regulatory functions in inflammation and adaptive immunity, its intrinsic role in T cells and autoimmunity has yet to be fully elucidated. Here we used CD4-PPARγKO mice to investigate PPARγ-deficient T cells, which were hyper-reactive to produce higher levels of cytokines and exhibited greater proliferation than wild type T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…Higher levels of PPARγ have been reported in SLE lymphocytes (57) and PPARγ agonist treatment of T cells from SLE patients induces transcriptional repression of genes involved in T cell activation, with those related to Th1 differentiation most affected (58). Mice lacking PPARγ only in CD4 + T cells develop an autoimmune phenotype characterized by expansion of Tfh cells, resulting in increased GC B cells, production of anti-DNA autoantibodies, and glomerular inflammation (59). Based on our finding that Th1 and Tfh cells are reduced in Sle123 →ApoA-I tg mice (Figure 4B–C), it is possible that PPARγ activation by 13-HODE and/or 9-HODE in lymphocytes may be a mechanism for ApoA-I mediated immune suppression, reducing T cell activation and subsequent expansion of Th1 and Tfh CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of PPARγ have been reported in SLE lymphocytes (57) and PPARγ agonist treatment of T cells from SLE patients induces transcriptional repression of genes involved in T cell activation, with those related to Th1 differentiation most affected (58). Mice lacking PPARγ only in CD4 + T cells develop an autoimmune phenotype characterized by expansion of Tfh cells, resulting in increased GC B cells, production of anti-DNA autoantibodies, and glomerular inflammation (59). Based on our finding that Th1 and Tfh cells are reduced in Sle123 →ApoA-I tg mice (Figure 4B–C), it is possible that PPARγ activation by 13-HODE and/or 9-HODE in lymphocytes may be a mechanism for ApoA-I mediated immune suppression, reducing T cell activation and subsequent expansion of Th1 and Tfh CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ-deficient T cells also have increased levels of cytokines and NF-κB activity following TCR stimulation. 90 This inhibitory role of PPARγ in T-cell activation is observed in female PPARγ-deficient T cells, but not in male T cells, suggesting that PPARγ is more important in females for NF-κB regulation. In addition, female PPARγ-deficient T cells produce enhanced lineage-specific cytokines in Th1, Th2, Th17 and Th9 cells under T-cell-differentiation-skewing conditions.…”
Section: Sex-specific Pparγ-dependent Differences In Immune Responsesmentioning
confidence: 95%
“… 90 The expression of PPARγ is also increased in CD4 + T cells following TCR stimulation. 56 , 90 PPARγ expression is also higher in female T cells than in males, 33 , 56 , 91 and the treatment of male T cells with estradiol enhances the expression of PPARγ, suggesting that the female sex hormone estrogen profoundly influences the expression of PPARγ in T cells. These data may also suggest that PPARγ may be more sensitively regulated by PPARγ ligand treatment in female T cells than in male T cells.…”
Section: Sex-specific Pparγ-dependent Differences In Immune Responsesmentioning
confidence: 99%
“…Interestingly, we also reported that PPARγ-deficient T cells in males are more apoptotic, with reduced T FH responses or no significant phenotype in T cell differentiation in vitro, while PPARγ-deficient T cells in females are more easily activated and differentiate into Th1, Th2, Th17, and T FH cells [31]. …”
Section: Introductionmentioning
confidence: 99%